Effect Of Competency, Training, Work Environment, Work Motivation, And Discipline On Employee Performance At Dinas PUPR Kepahiang - Prawijaya, Bambang Siswan; Anzori, Anzori; Kresnawati, Kresnawati (UNIVED Press, 2026)
This study aims to analyze the influence of competence, training, work environment, work motivation, and work discipline on the performance of employees of the Public Works and Spatial Planning Agency (PUPR) of Kepahiang Regency. The study uses a quantitative approach with survey methods and multiple linear regression analysis. Primary data were collected through the distribution of questionnaires to a total of 77 respondents, consisting of employees working in various fields and roles. The results show that each variable; competence, training, work environment, work motivation, and work discipline; has a positive influence on employee performance, both partially and simultaneously. Regression analysis results indicate that the work environment variable has the most dominant influence on performance improvement, followed by competence, work motivation, work discipline, and training. These results indicate the importance of improving employee competence through continuous and sustainable training, creating a comfortable and safe work environment, fostering work motivation, and enforcing work discipline for effectiveness and efficiency in work. This study provides practical implications for the Public Works and Spatial Planning Office (PUPR) of Kepahiang Regency in formulating strategic policies to strengthen human resource quality and organizational performance in the local government sector.